Active learning for elementary school based on GeoGebra in SD Swasta Islam Terpadu IQRA’ - Maulida Yanti; Rosmaini, E; Herawati, E; Pane, R; Sutarman (Talenta Publisher, 2020)
Mathematics is a difficult subject for some elementary school students. One of the reasons is because the teacher still uses traditional methods using textbooks and blackboards so that sometimes it doesn't attract students' interest. Teacher's role in creating a more interactive and interesting learning atmosphere is needed. GeoGebra is an application can be used as an interactive learning medium for Mathematics lessons. This community service will provide training on active learning for Elementary School level using GeoGebra at SD Swasta Islam Terpadu IQRA’. Training about GeoGebra was given to a group of teachers who teach Mathematics. The training included how to install GeoGebra application, how to create basic objects and how to make animations using sliders in GeoGebra. Furthermore, GeoGebra training can also be given to other schools as an alternative to a more interactive mathematics learning media.